Monocyte to high‐density lipoprotein cholesterol ratio as an independent risk factor for papillary thyroid carcinoma. Issue 11 (21st September 2021) - Xu, Hongzhi; Pang, Yufeng; Li, Xueqing; Zha, Bingbing; He, Tao; Ding, Heyuan
Abstract: Background: Papillary thyroid carcinoma (PTC) is considered to be an inflammatory disease. This study aimed to investigate the association of monocyte to high‐density lipoprotein cholesterol ratio (MHR) with PTC. Methods: Clinical parameters from 300 patients with PTC and 552 patients with benign thyroid nodule were compared. Serum renal function and liver enzymes, fasting plasma glucose, lipid profile, and blood cell count were measured. Results: Patients with PTC had a higher MONO ( p  < 0.001) and MHR ( p  < 0.001). There was a step‐wise increase in the prevalence of PTC ( p  = 0.003) with the tertile of MHR. Logistic regression analysis revealed that MHR could be considered an independent risk factor ( p  < 0.001) in the case‐control study and the cohort study. Pearson correlation analysis and simple linear regression analysis indicated that MHR was positively associated with neutrophil (NEU) and lymphocyte (LYM) count as well as neutrophil‐to‐lymphocyte ratio (NLR). Area under the curve (AUC) was 0.711. The optimal cutoff of MHR was 0.33 × 10 9 /mmol. Conclusion: This study identifies novel evidence that patients with PTC have a higher MHR. MHR is an independent risk factor for PTC. These findings support the application of MHR to predict, diagnose, and evaluate the occurrence of PTC. Abstract : Prevalence of PTC among three groups categorized by tertile of MHR. There was a step‐wise increase in the prevalence of PTC (30.4% vs 32.3% vs. 42.7%, p  = 0.003) with MHR tertile.